Comparative Study Of Yield Performance Of Two Important Clones Of Rubber -RRii 105 And RRIM 600 In Mooply Valley Of Thrissur District - Perumal Pillai S (Department of Plantation Crops and Spices, College of Horticulture, 1992)
A comparative study of the yield performance of two high yielding clones. RRII 105 and RRIM 600 were made. The former one is recommended under category I irrespective of areas and the latter as category II in traditional areas and as category I in nontraditional areas. Two representative samples where both these clones were planted and under tapping for a pretty long period were selected and all the available data pertaining to yield were collected. The agroclimatic conditions in both the estates are similar. They were following the recommended package of practices by Rubber Board. The severity of the diseases were reduced by timely adoption of prophylactic/control measures. From the study it was observed that RRII 105 is superior to RRIM 600 in yield performance as well as in some of the secondary characters which are desirable for good planting materials. The results of the study indicated that both the clones can be safely recommended for planting in the Mooply Valley area of Thrissur district., giving more preference and greater area for RRII 105. This study also supports the recent changes made by the Rubber Board in the planting material recommendations under category I.